Influence of the type of pre-calcined asbestos containing wastes on the properties of sintered ceramics. (1st March 2016) - Kusiorowski, Robert; Zaremba, Teresa; Piotrowski, Jerzy
Highlights: New interesting possibility for cement-asbestos wastes utilisation. Asbestos containing wastes thermally pre-treatment as an useful secondary raw material for production of sintered ceramics. The preparation of dry ceramic masses eliminates the efflorescence formation on the surface of the ceramics. Asbestos-cement wastes heat pre-treated at different temperature influence on the ceramic properties. Abstract: The paper presents the issue of using asbestos-containing materials as well as one of the possible methods that allows to change the dangerous properties of asbestos in cement-asbestos ("eternit") to a harmless material that can be used in further applications. The article presents the experimental results in which the possibility of cement-asbestos use as a secondary raw material for the manufacture of sintered ceramics (clinker ceramics) as well as the influence of the pre-calcined cement-asbestos type were studied. Three variants of cement-asbestos waste were used: raw, without any thermal treatment or after previous calcination at selected temperatures (700 and 1200 °C). These materials were added (0–10 wt%) to commercial mixtures (ceramic mass) to produce sintered ceramics. Green compacts were formed from dry ceramic masses (with a limited amount of mixing water) and were then sintered. After the firing cycle, ceramic properties such as linear shrinkage, water absorption, open porosity, apparent density, compressive strength and freeze resistance were determined. The results of the study show that cement-asbestos material can be used as an interesting secondary raw material to produce sintered ceramics. The obtained ceramics samples were characterised by low water absorption, high compressive strength and full frost resistance. The type of introduced cement-asbestos material had an influence on the ceramic properties.